Botulinum Toxin a Valuable Prophylactic Agent for Migraines and a Possible Future Option for the Prevention of Hormonal Variations-Triggered Migraines - Dima Lorena; Balan Andreea; Moga Marius Alexandru; Dinu Catalina Georgeta; Dimienescu Oana Gabriela; Varga Ioana; Neculau Andrea Elena (Toxins, 2019)
Background: In 1989, Botulinum toxin (BoNT) was accepted by the FDA for the management of some ophthalmic disorders. Although it was initially considered a lethal toxin, in recent times, Botulinum toxin A (BoNT-A), which is the more used serotype, has expanded to cover different clinical conditions, primarily characterized by neuropathic pain, including migraines and headaches. Evidence suggests that migraines are influenced by hormonal factors, particularly by estrogen levels, but very few studies have investigated the prevalence and management strategies for migraines according to the hormonal status. The effects of several therapeutic regimens on migraines have been investigated, but the medications used varied widely in proven efficacies and mechanisms of action. BoNT-A is increasingly used in the management of migraine and several placebo-controlled trials of episodic and chronic migraine are currently underway. This paper is a review of the recently published data concerning the administration of BoNT-A in the prevention of chronic migraines. Considering the lack of population-based studies about the e ectiveness of BoNT-A in the alleviation of premenstrual and perimenopausal migraines, this study proposes a new perspective of the therapeutic approach of migraine syndrome associated with menopausal transition and the premenstrual period. Methods: We selected the reviewed papers from CrossRef, PubMed, Medline, and GoogleScholar, and a total of 21 studies met our inclusion criteria. Results: To date, no specific preventive measures have been recommended for menopausal women with migraines. BoNT-A often reduces the frequency and intensity of migraine attacks per month; the treatment is well tolerated and does not exhibit a significantly higher rate of treatment-related side effects. No population-based studies were conducted in order to highlight the role of BoNT-A in menopause-related migraines, neither in menstrual migraines. Conclusion: There is a need for further research in order to quantify the real burden of menstrual and perimenopausal migraines and to clarify if BoNT-A could be used in the treatment of refractory postmenopausal and premenstrual migraines.
Keywords: Botulinum toxin type A; premenstrual migraine; chronic migraine; menopausal transition; neuropathic pain